2013
DOI: 10.1073/pnas.1309247110
|View full text |Cite
|
Sign up to set email alerts
|

Maurer's clefts, the enigma of Plasmodium falciparum

Abstract: Plasmodium falciparum, the causative agent of malaria, completely remodels the infected human erythrocyte to acquire nutrients and to evade the immune system. For this process, the parasite exports more than 10% of all its proteins into the host cell cytosol, including the major virulence factor PfEMP1 (P. falciparum erythrocyte surface protein 1). This unusual protein trafficking system involves long-known parasitederived membranous structures in the host cell cytosol, called Maurer's clefts. However, the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 119 publications
0
87
0
Order By: Relevance
“…Because PfPMV has a unique substrate specificity [6], the remaining but functionally uncharacterized PfPMX and PfPMIX enzymes [25] are now at the top of the list as possible targets for HIV PIs in malaria. These 'late' plasmepsins are expressed before parasite egression and are localized to the peripheral parts of the host secretory machinery -Maurer's clefts of infected erythrocytes [26]. They have also been found to interact with P. falciparum proteins that are known to localize to the host erythrocyte cytoplasm [27].…”
Section: Plasmodium Falciparummentioning
confidence: 99%
“…Because PfPMV has a unique substrate specificity [6], the remaining but functionally uncharacterized PfPMX and PfPMIX enzymes [25] are now at the top of the list as possible targets for HIV PIs in malaria. These 'late' plasmepsins are expressed before parasite egression and are localized to the peripheral parts of the host secretory machinery -Maurer's clefts of infected erythrocytes [26]. They have also been found to interact with P. falciparum proteins that are known to localize to the host erythrocyte cytoplasm [27].…”
Section: Plasmodium Falciparummentioning
confidence: 99%
“…One of these membranous compartments is the parasitophorous vacuole membrane that surrounds the parasite during the entire intraerythrocytic life cycle and that separates the parasite from the erythrocyte cytosol. Another group of membranous compartments is the Maurer's clefts, small vesicles that are important for the transfer of parasite proteins to the surface of the infected cell (26, 27). As mature erythrocytes are devoid of internal membranes and lack the capacity to produce membranes (28), these newly formed membranes, which are all outside of and unconnected to the parasite, must be produced by the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that a parasite-encoded protein, skeleton-binding protein 1 (SBP1), is essential for trafficking and translocation of PfEMP1 onto the RBC surface and consequently for adhesion of PRBCs to the vascular endothelium [10,11]. SBP1 is a trans-membrane protein, located in parasite-induced membranous structures within the PRBC cytoplasm known as Maurer's clefts (MCs) [12,13]. The topology of SBP1 is such that its entire N-terminal domain (SBP1-N; Fig.…”
Section: Introductionmentioning
confidence: 99%